Chloroplast DNA Variations in Wild Brassicas and Their Implication in Breeding and Population Genetics Studies - Bharti Sarin; Juan Pedro Martín; Babeeta Chrungu Kaula; Aparajita Mohanty (Scientifica)
Evaluation of chloroplast DNA (cpDNA) diversity in wild relatives of crop brassicas is important for characterization of cytoplasm and also for population genetics/phylogeographic analyses. The former is useful for breeding programs involving wide hybridization and synthesis of alloplasmic lines, while the latter is important for formulating conservation strategies. Therefore, PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) technique was applied to study cpDNA diversity in 14 wild brassicas (including 31 accessions) which revealed a total of 219 polymorphic fragments. The combination of polymorphisms obtained by using only two primer pair-restriction enzyme combinations was sufficient to distinguish all 14 wild brassicas. Moreover, 11 primer pairs-restriction enzyme combinations revealed intraspecific polymorphisms in eight wild brassicas (including endemic and endangered species, B. cretica and B. insularis, resp.). Thus, even within a small number of accessions that were screened, intraspecific polymorphisms were observed, which is important for population genetics analyses in wild brassicas and consequently for conservation studies.